Cavity-enhanced narrowband spectral filters using rare-earth ions doped in thin-film lithium niobate - Yuqi Zhao; Dylan Renaud; Demitry Farfurnik; Yuxi Jiang; Subhojit Dutta; Neil Sinclair; Marko Lončar; Edo Waks (npj Nanophotonics)
Abstract On-chip optical filters are fundamental components in optical signal processing. While rare-earth ion-doped crystals offer ultra-narrow optical filtering via spectral hole burning, their applications have primarily been limited to those using bulk crystals, restricting their utility. In this work, we demonstrate cavity-enhanced spectral filtering based on rare-earth ions in an integrated nonlinear optical platform. We incorporate rare-earth ions into high quality-factor ring resonators patterned in thin-film lithium niobate. By spectral hole burning at 4 K in a critically coupled resonance mode, we achieve bandpass filters ranging from 7 MHz linewidth, with 13.0 dB of extinction, to 24 MHz linewidth, with 20.4 dB of extinction. By reducing the temperature to 100 mK to eliminate phonon broadening, we achieve an even narrower linewidth of 681 kHz, which is comparable to the narrowest filter linewidth demonstrated in an integrated photonic device, while only requiring a small device footprint. Moreover, the cavity enables reconfigurable filtering by varying the cavity coupling rate. For instance, as opposed to the bandpass filter, we demonstrate a bandstop filter utilizing an under-coupled ring resonator. Such versatile integrated spectral filters with high extinction ratio and narrow linewidth could serve as fundamental components for optical signal processing and optical memories on-a-chip.